Abnormal functional connectivity of the amygdala in first-episode and untreated adult major depressive disorder patients with different ages of onset. Issue 4 (1st March 2017) - Ye, Jing; Shen, Zonglin; Xu, Xiufeng; Yang, Shuran; Chen, Wei; Liu, Xiaoyan; Lu, Yi; Liu, Fang; Lu, Jin; Li, Na; Sun, Xuejin; Cheng, Yuqi
Abstract : Major depressive disorder (MDD) is a common mental disorder with high morbidity. As a part of the limbic system, the amygdala is important in the processing of emotional information. Structural and functional connectivity (FC) abnormalities in the amygdala have been observed in MDD patients. The present study was carried out to identify the features of amygdala FC in adult MDD patients with different ages of onset. Sixty-nine first-episode and untreated MDD patients and 81 healthy controls (CTLs) were included in this study and underwent 3D structural imaging and resting-state functional MRI scanning. The patients and CTLs were divided into two groups according to age of onset: young adult (<30 years old) and old adult (≥30 years old). Voxel-based morphometry methods were used to investigate volume differences in MDD patients with different ages of onset at the whole-brain level. Then, the resting-state FC of bilateral amygdala seeds to the whole brain of MDD patients and matched CTLs in these two different onset age groups were analysed. We found that the volume of the bilateral amygdala increased to a greater extent in young adult patients compared with old adult patients. We also observed a trend toward different amygdala FC by onset age in MDD patients. In young adult patients, the left amygdala showed more abnormal resting-state FC with other regions compared with matched controls. However, in old adult patients, compared with matched controls, the right amygdala showed more abnormal changes in the resting-state FC with other regions. MDD patients with different ages of onset showed different changes in the structure and FC of the amygdala. These results might help us to understand the high heterogeneity of MDD.